POTENSI FRAKSI ETIL ASETAT KULIT BATANG KESAMBI SEBAGAI ANTIBAKTERI TERHADAP Escherichia coli THE POTENTIAL OF ETHYL ACETATE FRACTION OF KESAMBI STEM AS ANTIBACTERIAL AGAINST Escherichia coli - Afif Hidayatul Mustafid; Yeyen Maryani; Sri Agustina; Boima Situmeang (Tanjungpura University, 2023)
In our previous research, ethyl acetate extract of kesambi stem bark have the highest antibacterial activity against Escherichia coli compared with n-hexane and methanol extract. In our present study, we report the antibacterial activity of fractions from ethyl acetate extract against Escherichia coli. The method of fractionation used coloumn and thin lawyer chromatography. The Antibacterial activity uses Kirby Bauer methods. The characterization of active fractions used spectrometer infrared. The result showed fractions 6 and 7 have the highest antibacterial activity with inhibition zone 11.65 and 7.1 mm. The characterization of fractions 6 and 7 showed fungtional groups C=O, O-H, and C=C. The ethyl acetate fraction has the potential as antibacterial materials.